(untitled) (Research, Society and Development, 2021)
Formal Environmental Education is the most effective channel for developing citizenship in the individual and the continuous reflection on the role that he/she plays in society. The Ecological Footprint can be defined as a measure of sustainability, within the scope of quantifying natural resources and providing data for the analysis of the carrying capacity of the land. In this context, this research aimed to evaluate the population’s perception of the ecological footprint in the city of Campina Grande-Paraíba. The technique used in the research was documentary, bibliographical, with a qualitative and quantitative character. Data from the 2021 School Census were collected and a questionnaire with 10 (ten) objective questions was applied to a group of 47 people. As a result, it was found that the Ecological Footprint effectively contributes to the recognition of environmental problems, but it is still beyond the knowledge of many of the respondents. It was also found that, even though the school is the greatest aggregator of plurality of knowledge, there is still a lot to be done by uniting the environment with education.